An integrated framework approach for PPP projects in Egypt - Mohy El Din, Nada Sherin (AUC Knowledge Fountain, 2017)
Public-Private Partnership (PPP) projects have been growing over the last decade in Egypt, with an increasing popularity and interest in the participation of different entities in similar projects. Since the government is not considered the only provider for public infrastructure systems, the private sector is now contributing to providing such services. However, not all PPP projects have been equally successful or have been utilized in the best way through planning and decision. PPP projects require full consideration of all the factors, adequate structuring and the correct adoption of such factors. Failure in the consideration of all factors that complete the life cycle of PPPs may lead to the failure of the project. An integrated approach within a framework is required in order for the PPP projects to succeed. Limited research has presented an integrated framework approach for the adoption of PPPs. The framework for PPP projects should be conducted both simultaneously and iteratively for the project to succeed. The objective of this study is to assist the government in the front end process of a PPP project, while contributing to the general understanding and filling some gaps in the research and study of such projects. This can be achieved by depicting an integrated framework approach for government adoption of PPP projects through three steps; the technical structure of the project, developing a financial model and finally, designing the procurement strategy of the PPP project. These three steps are the pillars that indicate the success or failure of a PPP project. These three pillars are then subdivided into a series of steps that form the integrated framework approach. Each pillar has a methodology that is followed by an application on a case study, and a validation exercise. The first pillar is the first step in the initial assessment of a PPP project. The technical structuring of the project includes structuring of the contractual terms and managing of risks. It is concluded that the termination term is one of the most important clauses in a PPP contract. In addition, financing risk is a risk that affects the affordability and the bankability of a PPP project, and it is allocated to the government. The second step in the initial assessment of a PPP project is the development of the public sector comparator. The second pillar is the financial modeling of a PPP project. A financial model template is developed, applied, and validated on a case study. The results reveal that the template is running properly and all financial formulas and equations are correct. Following the financial model development, a value for money assessment process is conducted on a case study both quantitatively and qualitatively. The risk-adjusted net present costs are calculated at different discount rates (10%, 11%, 12%, 13%, and 14%) for the public sector comparator and PPP option. The final pillar is a qualitative assessment of the procurement activities of PPP projects. According to law 67 that regulates PPP activities, the results show that single bid may be accepted if other qualified bidders have failed technically and it appears that the bid was made in the bidder’s belief under competition. Due to the complexity and long concession periods of PPP projects, technical offers shall have higher weight than financial offers. According to common practice, technical offers usually weigh 70% while financial offers weigh 30%. The concept of structuring a procurement process is further examined and validated by a case study.